2013
DOI: 10.5935/1808-8694.20130133
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Type 5 Inhibitors and sudden sensorineural hearing loss

Abstract: Increased occurrence in clinical practice and scientific reports in the literature suggest that the phosphodiesterase type 5 inhibitors are considered a risk factor for sudden deafness. Further studies with larger samples and control groups are needed for better assessing this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
1
12
0
3
Order By: Relevance
“…Prior evidence related to this topic has been limited to infrequent cases in clinical trials, case reports, small clinical studies, and pharmacovigilance data from regulatory agencies . Common to all previous reports is the small sample size, limiting their abilities to quantify the risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior evidence related to this topic has been limited to infrequent cases in clinical trials, case reports, small clinical studies, and pharmacovigilance data from regulatory agencies . Common to all previous reports is the small sample size, limiting their abilities to quantify the risk.…”
Section: Discussionmentioning
confidence: 99%
“…safety signal, the FDA approved more stringent labeling alerting to the potential risk of sudden hearing loss in men by using PDE5 inhibitors. 7 Since then, additional data from mouse model, [10][11][12] case reports, [13][14][15] small clinical studies, 16,17 and pharmacovigilance 18 have been published, raising further concern. While the association is perhaps initially surprising, a plausible mechanism for PDE5 inhibitor ototoxicity involves the nitric oxide-cyclic guanosine monophosphate signaling pathway 13 that has also been implicated with ototoxicity of gentamicin and cisplatin 19,20 To date, no large postmarketing safety studies of PDE5 inhibitor ototoxicity have been reported.…”
mentioning
confidence: 99%
“…In 2012, unilateral sudden sensorineural hearing loss affecting two male PDE5 inhibitor users (age 37 and 43) was described by Barreto and Bahmad [27]. Unfortunately, neither the time after the hearing loss has occurred nor the dosage of PDE5 inhibitors was stated.…”
Section: Phosphodiesterase-5 (Pde5) Inhibitorsmentioning
confidence: 99%
“…O mesmo ocorreu em um estudo clínico de 2009 [80] . Um estudo de coorte de 2010, avaliando 11.525 homens, com 40 anos ou mais, por 2 anos, mostrou que a perda auditiva foi duas vezes mais comum entre utilizadores dos inibidores de PDE-5 82 . Mais estudos a respeito são necessários, mas alguma relação já é observada e precisa ter a atenção médica 78,80,81 .…”
Section: -Inibidores Da Pde-5 E Perda Auditivaunclassified